Enhanced Rhamnolipid Production From Waste Cooking Oil By Pseudomonas Aeruginosa Usm-Ar2 - Samsu, Zainatul `Asyiqin (2019)
Rhamnolipid, a glycolipid type of biosurfactant is the most investigated glycolipid biosurfactant. The problem of this study was the waste cooking oil used as a major carbon source is immiscible in aqueous phase and inhibited the growth of the microorganisms studied which is Pseudomonas aeruginosa USM-AR2. The ultimate aim is to enhance microbial production of rhamnolipid on a lab-scale. Thus, the appropriate feeding strategy for fed-batch culture needs to be determined to increase the availability and subsequent intake of the carbon source by the microorganisms. Several objectives have to be met to ensure this strategy is achievable, which include: 1) to evaluate and select different medium formulation from literature.; 2) to determine the effect of operational conditions on rhamnolipid production and the behaviour of oxygen transfer in batch culture; 3) to analyse the kinetics of rhamnolipid production in batch culture; and 4) to identify the best feeding strategy to improve rhamnolipid production in fed-batch culture. Results showed that the modified medium composition to support rhamnolipid production contained the following: NO3-, Mg+, K+, PO43-, trace elements and waste cooking oil with C/N equivalent to 18. The addition of Tween 80, a commercial surfactant, into the medium showed no significant impact on rhamnolipid production. In a bench-top bioreactor, the agitator tip speed affected rhamnolipid production. Rhamnolipid production at a lower tip speed (1.131 m/s) was 1.5-fold higher than production at a higher tip speed (1.414 m/s). Rhamnolipid production achieved the maximum concentration of 4.86 g/L (0.041 g/L.h of the overall productivity) when the production medium was controlled at pH 6.85.